CFA-18: a homochiral metal–organic framework (MOF) constructed from rigid enantiopure bistriazolate linker molecules. Issue 44 (4th November 2020) - Knippen, Katharina; Bredenkötter, Björn; Kanschat, Lisa; Kraft, Maryana; Vermeyen, Tom; Herrebout, Wouter; Sugimoto, Kunihisa; Bultinck, Patrick; Volkmer, Dirk
Abstract : In this work, we introduce a novel enantiopure chiral spiro bistriazolate linker molecule ( H 2 - bibta ) and the corresponding first enantiopure bistriazolate-based metal–organic framework, CFA-18 (Coordination Framework Augsburg-18 ). Abstract : In this work, we introduce the first enantiopure bistriazolate-based metal–organic framework, CFA-18 (Coordination Framework Augsburg-18 ), built from the R -enantiomer of 7, 7, 7′, 7′-tetramethyl-6, 6′, 7, 7′-tetrahydro-3 H, 3′ H -5, 5′-spirobi[indeno[5, 6- d ]-[1, 2, 3]triazole] ( H 2 - spirta ). The enantiopurity and absolute configuration of the new linker were confirmed by several chiroselective methods. Reacting H 2 - spirta in hot N, N -dimethylformamide (DMF) with manganese(ii ) chloride gave CFA-18 as colorless crystals. The crystal structure with the composition [Mn2 Cl2 ( spirta )(DMF)2 ] was solved using synchrotron single-crystal X-ray diffraction. CFA-18 shows a framework topology that is closely related to previously reported metal–azolate framework (MAF) structures in which the octahedrally coordinated manganese(ii ) ions are triazolate moieties, and the chloride anions form crosslinked one-dimensional helical chains, giving rise to hexagonal channels. In contrast to MAFs crystallizing in the centrosymmetric space group R 3̄, the handedness of the helices found in CFA-18 is strictly uniform, leading to a homochiral framework that crystallizes in the trigonal crystal system within the chiral space group P 31 21 (no. 152).